Associations of bifenthrin exposure with glucose homeostasis and type 2 diabetes mellitus in a general Chinese population: Roles of protein carbonylation. (15th December 2022) - Liang, Ruyi; Yu, Linling; Liu, Wei; Dong, Chaoqian; Tan, Qiyou; Wang, Mengyi; Ye, Zi; Zhang, Yongfang; Li, Minjing; Wang, Bin; Feng, Xiaobing; Zhou, Min; et al.
Abstract: The adverse health effects of pyrethroids exposure have attracted wide concern. We aimed to assess the associations of bifenthrin, a widely used pyrethroid, with glucose homeostasis and risk of type 2 diabetes mellitus (T2DM) and to explore the underlying mechanism. Serum bifenthrin, fasting plasma glucose (FPG), fasting plasma insulin (FPI), and plasma protein carbonyl (PCO) were determined among 3822 participants from the Wuhan-Zhuhai cohort. Glucose homeostasis was evaluated by FPG, FPI, homeostasis model assessment of insulin resistance (HOMA-IR), impaired fasting glucose (IFG), and abnormal glucose regulation (AGR). The associations of serum bifenthrin with glucose homeostasis and risk of T2DM were assessed by generalized linear models and logistic regression models. The role of PCO in the above associations was evaluated by mediation analyses. After adjusting for covariates, each 2-fold increase in serum bifenthrin was associated with a 0.21 mmol/L increase in FPG and a 5.19%, 10.49%, and 12.18% increase in FPI, HOMA-IR, and PCO levels, respectively. Monotonically elevated ORs of IFG and AGR (all P and P for trend <0.05), but not T2DM ( P > 0.05) were detected to be associated with increased bifenthrin. Compared with the participants with low bifenthrin and low PCO, participants with high bifenthrin exposure and high PCO showed a 0.40 mmol/L, 11.07%, and 22.50% increase in FPG, FPI, and HOMA-IR, as well as a 119.97% and 48.88% increase in risks of IFG and AGR, respectively ( P for trend <0.05). Moreover, PCO mediated 13.61%–24.98% of the serum bifenthrin-associated glucose dyshomeostasis. The study suggested that bifenthrin exposure was dose-dependently associated with glucose dyshomeostasis in the general Chinese urban adults, and these associations were exacerbated and partly mediated by PCO. Given that other pollutants were not included in this study, the effect of co-exposure of pyrethroids with multiple pollutants is necessary to be considered in future studies. Graphical abstract: Image 1 Highlights: Serum bifenthrin was dose-dependently associated with glucose dyshomeostasis. Protein carbonylation exacerbated bifenthrin-associated glucose dyshomeostasis. Protein carbonylation partly mediated bifenthrin-associated glucose dyshomeostasis.